Real-time quantitative polymerase chain reaction (QPCR) for the identification and quantification of Streptococcus Mutans in saliva and dental biofilm in children - Moncada-Cortés, Gustavo Adolfo; Duperat, Lorena del Carmen; Palma, Patricia; Corsini, Gino; Neira, Miguel; Reyes, Evelyn; Oliveira-Junior, Osmir Batista; Faleiros, Simone; Gordan, Valeria; Yévenes, Ismael (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: the objective of this study was to use real-time qPCR to identify and quantify the Streptococcus mutans species in samples of saliva and dental biofilm. Methods: 27 children were randomly chosen with the following criteria: 8 years of age, low socio-economic levels, residing in the northern metropolitan area of Santiago de Chile; they were asked to attend an appointment while fasting with no teeth brushing for at least 12 hours, in order to collect non-stimulated saliva and a pool of supragingival dental biofilm of all the mesio-vestibular sides of anterior and posterior teeth. The amount of S. mutans in the samples was quantified by qPCR using primers that amplify a fragment of the gtfB gene of S. mutans. Results: the amplification showed 98% efficiency with a fluorescence of 3.36 cycles. The melting curve presented a single maximum at the same temperature for all samples. Conclusion: the methodology allows the specific identification and quantification of gene gtfB of S. mutans in saliva and dental biofilm in a quick and reliable manner, contributing to the identification of individual cariogenic risk.